The effect of aromatic aminoalcohols on UV-cured films - Arsu, Nergis; Karasu, Feyza; Balta, Demet Karaca; Temel, Gokhan (ELSEVIER SCIENCE SA, 2009)
It has been shown that the following three substituted alpha-aminoalcohols, 2-(N-methyl-N-phenylamino-1-phenyl) ethanol (1), 2-methyl-1-[4-(methylthio) phenyl-2-morpholino]propane-1-ol(2) and 2-benzyl-2dimethylamino-1-(4-morpholinophenyl)-butan-1-ol (3) fragment upon irradiation to give radicals which initiate polymerisation of trimethylolpropane triacrylate (TMPTA). The effectiveness of aminoalcohol (1) as an amelioration of oxygen inhibition was investigated and found to be less effective than N-methyldiethanolamine. Aminoalcohol (1) is a good synergist for isopropylthioxanthone but due to the, absorption characteristic of benzophenone, which absorbs poorly above 300 nm, it is not a suitable initiator. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Aromatic aminoalcohols; Photoinitiator; Photopolymerisation; UV-curing; FREE-RADICAL POLYMERIZATION; PHOTOINITIATION; Chemistry; Materials Science